Exploring clause awareness through song lyrics: EFL learners’ challenges and perceptions in contextualized grammar instruction - Sheila Agustina; Fika Megawati; Vevy Liansari; Sholikhatul Mu’Minin; Suhailah Himmatul Ulya (University of Muhammadiyah Malang, 2025)
Traditional grammar instruction in EFL classrooms oftenemphasizes rule memorization and mechanical drills, which limitstudents’ ability to apply grammatical knowledge in authenticcontexts. To address this gap, the present study explores theuse of English song lyrics as authentic material to developclause awareness, focusing on students’ ability to identify noun,adjective, and adverbial clauses. Forty-third-semesterundergraduate students at an Indonesian university analyzedselected song lyrics to identify clause types, followed by a focusgroup discussion with five volunteers. Analysis of students’ workshowed that over 83% adverbial clauses were successfullyidentified, followed by noun (70.8%) and adjective clauses(60%). The success is often aided by recognizable subordinatorssuch as ‘because’ and ‘when’. Meanwhile, errors werecommonly linked to blurred syntactic boundaries, poeticcompression, and the absence of standard punctuation in lyrics.These results demonstrate that song lyrics can enhance clauserecognition, particularly for adverbials, but require scaffoldingfor more complex clause functions. Beyond task performance,focus group discussions revealed that students found theactivity engaging and motivating, confirming earlier claimsabout the affective benefits of music in language learning.Unlike previous studies that emphasize songs for vocabulary orlistening, this study highlights their potential for explicitgrammar instruction, contributing evidence of both cognitivegains and affective value. The findings support the integrationof multimodal, student-centered materials into grammarpedagogy to promote deeper syntactic awareness and learnerengagement in EFL contexts.